The Role of Indonesia’s Forest Area with Special Purpose in Supporting Sustainable Development Goals - Muhammad Iqbal Nur Madjid; Rissa Rahmadwiati; Rezky Lasekti Wicaksono; Dwi Apriyanto (Research in Ecology, 2025)
Forest areas with special purpose (FASP) are decentralized management rights of state forest areas for universities and research institutions. The area of FASP management licenses continues to increase, as recorded in 2019, covering an area of 37,569 ha. At the end of 2024, there are 45 FASPs in Indonesia with a total area of 107,085.91 ha. The management of FASP is expected to achieve its main objectives of education and research, without leaving the ecological function as the main function of the forest. Various studies have been conducted in FASP on different research topics, but none of them have summarized the role of FASP in supporting sustainable development goals. This study aims to determine the role of FASP in Indonesia in supporting the implementation of SDGs. This research was conducted through a systematic literature review using articles from the Scopus and Web of Science databases. Through a series of data collection activities, 48 articles were obtained as review material in this study. The results of this study indicate that the FASP management that has been implemented in Indonesia not only supports educational and research objectives, but also supports the achievement of SDGs which are divided into 1) ecology and biodiversity (SDG 15), 2) community welfare (SDG 1, 2, and 5), 3) sustainable utilization (SDG 12), 4) climate change response (SDG 13), and 5) water and soil conservation (SDG 6). Further research can be conducted at different FASP locations to support information on the role of FASP in achieving the SDGs.